MODERN REQUIREMENTS FOR PROFESSIONAL ACTIVITY IN THE FIELD OF FINE ARTS - Yuldashev Ibroxim Tuychiyevich (Modern American Journals, 2025)
This article explores the modern requirements for professional activity in the field of fine arts, focusing on the dynamic transformations brought about by technological innovation, globalization, and evolving cultural values. The study highlights the multifaceted competencies contemporary artists must possess, including mastery of both traditional and digital tools, interdisciplinary approaches, and strong communication skills. The paper also addresses the critical role of modern education in fine arts, emphasizing the need for curriculum innovation, continuous practice, and the integration of digital and global market trends. The findings underscore the importance of preparing artists who are adaptable, technologically proficient, and culturally aware, ensuring their success in the 21st-century creative industries.
Keywords: Fine arts, professional competencies, digital technologies, interdisciplinary education, creative industries, curriculum innovation, global art market, cultural awareness, artistic identity, lifelong learning.